MAKTABGACHA YOSHDAGI BOLALARNI IJTIMOIY-PSIXOLOGIK KOMPITENSIYA VA AXLOQIY KO'NIKMALARINI RIVOJLANTIRISH (E Conference Zone, 2022)
This article provides information and recommendations for the development of sociopsychological competencies and moral skills of preschool children, which can be used by parents, future educators, teachers of MTT.